PENGARUH GAYA HIDUP, KUALITAS PRODUK, DAYA TARIK PROMOSI TERHADAP KEPUTUSAN PEMBELIAN TISU TESSA MELALUI CITRA MEREK (Studi Pada Mahasiswa S1 Fakultas Ekonomi dan Bisnis Universitas Diponegoro) - Pratidina, Nissa Gin Ajeng; Soesanto, Harry (Faculty of Economics and Business Diponegoro University, 2018)
The modernization of the lifestyle of a practical and fast-paced society, tissue is now a must-have or carry when traveling. The high competition of tissue production does not make PT Graha Kerindo Utama as Tessa producer afraid to produce environmentally friendly tissue. Although retail stores are now rampant circulating in Indonesia can be a threat and challenge because they are able to produce tissues with a cheaper price. This allows Tessa's tissue is no longer a top priority in consumer purchases. The purpose of this study was to analyze the influence of lifestyle, product quality, promotion to purchasing decisions through brand image. This study uses five variables those are lifestyle, product quality, promotion, brand image, and purchase decision.The study testing the hypothesis using the data as much as 102 respondents. Analytical techniques used in this study using software program SmartPLS version 2.0. This study was conducted to consumers who have used Tessa tissue, where the respondents are university student of bachelor Faculty of Economics and Business. The number of samples in this study were 102 respondents. Data collection method is done through questionnaire. sampling technique in this research is purposive sampling. This research uses Structural Equation Model (SEM) analysis technique, which is estimated using SmartPLS 2.0 program. The results of this studied indicate that lifestyle have positive and significant effect on brand image, product quality have positive and significant effect to brand image, attractiveness of promotion have positive and significant effect to brand image, brand image have positive and significant influence on purchasing decision, and significant to the purchase decision. While the attractiveness of promotion has a positive but not significant effect on purchasing decisions.